Dinuclear osmium complexes as mitochondrion-targeting antitumor photothermal agents in vivo. Issue 91 (26th October 2022) - Wang, Meng-Fan; Deng, Yu-Ang; Li, Qing-Fang; Tang, Shi-Jie; Yang, Rong; Zhao, Run-Yu; Liu, Fu-Dan; Ren, Xiaoxia; Zhang, Dan; Gao, Feng
Abstract : Mitochondrion-targeting dinuclear osmium complexes with extremely high photothermal conversion capability under irradiation of an 808 nm low-power laser without nucleus affinity and photodynamic activity act as antitumor photothermal therapy agents in vivo . Abstract : Four dinuclear osmium complexes have been constructed for antitumor phototherapy. The most potent Os4 has extremely high photothermal conversion capability under irradiation of an 808 nm low-power laser, targets mitochondria in human melanoma cells without nucleus affinity, and acts as an antitumor photothermal therapy agent in vitro and in vivo .